Pengaruh Motivasi Kerja dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai - Wargiatno; Hadi, Syamsul; Chandra Kirana, Kusuma (SMARTINDO, 2024)
The aim of this research is to contribute to the literature and conceptual model of the influence of work motivation and transformational leadership on employee performance with job satisfaction as a mediating variable. This type of research is quantitative research with a survey method. The number of samples studied in this study was 115 samples of employees of the DIY Marine and Fisheries Service. Census method, because the entire population is used as a sample, the data collection method used is a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) with the SmartPLS program. The results of this research show that work motivation and transformational leadership partially have a positive and significant effect on job satisfaction. Work motivation, transformational leadership and job satisfaction partially have a positive and significant effect on employee performance. Job satisfaction is able to mediate the influence of work motivation and transformational leadership on employee performance